Strategi Sukses Membangun UMKM Dengan Pemahaman Akan Standar Akuntansi Keuangan EMKM dan UU HPP di RW.04 Karet Tengsin Jakarta Pusat - Oktasari, Erita; Lisdawati, Lisdawati; Widyastuti Wulaningsih, Ririn; Lase, Hofandrik; Yulianto, Eka (Jurnal Indonesia Sosial Sains, 2022)
This activity is covered by the phenomenon of understanding of SAK EMKM by MSME actors which is still minimal due to the lack of socialization of understanding these policies and rules and their benefits for the MSME community. The Faculty of Economics and Business, Bung Karno University (hereinafter referred to as FEB UBK) plans and facilitates lecturers who wish to carry out community service activities. This is the basis for the Bung Karno University FEB Accounting Study Program to plan community service activities in each annual work plan. The purpose of community service activities at FEB Bung Karno University is to provide knowledge to the community of RW.04 Karet Tengsin Central Jakarta by conducting socialization in order to provide knowledge about EMKM financial accounting standards (SAK) and the HPP Law to MSME actors in the area of ​​RW.04 Karet Tengsin Jakarta Center.